Success Rate of Trabeculectomy in Primary Glaucoma at Cicendo Eye Hospital on January–December 2013 - Erva Monica Saputro; Maula Rifada; RB. Soeherman Herdiningrat (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Trabeculectomy is a surgical therapy for glaucoma to preserve visual function by lowering intraocular pressure (IOP). In some studies, the success of trabeculectomy in lowering IOP is greater than medication. Success is defined by IOP <21 mmHg, with or without glaucoma medication. Primary glaucoma based on the mechanism of aquous humor outflow is divided into primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG). This study aimed to know the success rate of trabeculectomy in POAG and PACG.Methods: This study was a descriptive study conducted at Cicendo Eye Hospital using medical record of POAG and PACG patients who underwent trabeculectomy surgery on January–December 2013 with minimal one month follow-up. Data collection was conducted during September 2014. Data processed in this study were 100 eyes from 76 patients with diagnosis POAG and PACG.Results: The success rate for trabeculectomy in POAG was 79% and PACG was 86%, failure (IOP ≥ 21 mmHg) 21% in POAG, and 14% in PACG for period 2013 at Cicendo Eye Hospital.Conclusions: The success rate of trabeculectomy at Cicendo Eye Hospital is good in one month, with or without glaucoma medication after surgery. [AMJ.2016;3(1):110–4] DOI: 10.15850/amj.v3n1.723